Русская культура: монография / Д. С. Лихачев - Лихачев Дмитрий Сергеевич (Искусство, 2000)
Рез. англ. Экземпляры: (20180920) / Инвентарный номер: / Цена: / Сис.шифр: 63.3(2Р) / Авт.знак: Л65 / ГРНТИ: 13.09 / ББК: 63.3(2Р)-7